2021
DOI: 10.3389/fvets.2021.630089
|View full text |Cite
|
Sign up to set email alerts
|

Association Between BoLA-DRB3.2 Polymorphism and Bovine Papillomavirus Infection for Bladder Tumor Risk in Podolica Cattle

Abstract: Blood samples from 260 unrelated cattle (132 animals affected by papillomavirus-associated bladder tumors and 128 healthy) were genotyped using the classic polymerase chain reaction/restriction fragment length polymorphism method to screen MHC class II bovine leukocyte antigen-DRB3. 2 polymorphism. The DRB3*22 allele was significantly (p ≤ 0.01) detected in healthy cattle, thus appearing to have a negative association (protective effect) with virus infection of the urinary bladder known to represent a bladder … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…Previous studies have shown that BoLA-DRB3 polymorphism in BLV-infected cattle is related to blood proviral load (PVL), infectivity, lymphoma, and in utero infection of calves [18,[23][24][25][26][27][28][29]. In addition to BLV, BoLA-DRB3 polymorphism is associated with infectious diseases such as bovine clinical mastitis, papillomavirus infection, herpes virus type 1 infection, and foot-and-mouth disease [30][31][32][33]. Therefore, the BoLA-DRB3 polymorphism is considered a useful gene in immunology.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that BoLA-DRB3 polymorphism in BLV-infected cattle is related to blood proviral load (PVL), infectivity, lymphoma, and in utero infection of calves [18,[23][24][25][26][27][28][29]. In addition to BLV, BoLA-DRB3 polymorphism is associated with infectious diseases such as bovine clinical mastitis, papillomavirus infection, herpes virus type 1 infection, and foot-and-mouth disease [30][31][32][33]. Therefore, the BoLA-DRB3 polymorphism is considered a useful gene in immunology.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, BPV-13 (86,130) and BPV-14 (131) have also been found in bovine urinary bladder tumors. Interestingly, recent data indicate that specific major histocompatibility complex class II alleles may protect against BPV infection and reduce the risk of bladder cancer in cattle (132). The BPV-1 E5 oncoprotein shows transforming properties in vitro and is able to induce cytoskeletal remodeling of murine and bovine cells (133).…”
Section: Bracken Fern and Bpv In The Etiology Of Bladder Tumorsmentioning
confidence: 99%
“…The polymorphism in this region is therefore associated with the variability in the immune responsiveness in different individuals to particular infectious diseases and economic traits such as reproduction 22) , colostrum and milk microbiota 23) , milk quality and production rate 5) . For infection disease, BoLA-DRB3 relates with mastitis 24,25) , tick-borne disease 26,27) , foot and mouth disease (FMD) 28) , bovine herpesvirus 1 (BoHV-1) 29) , bovine papillomavirus-induced bladder cancer 30) , but not relates with the bovine tuberculosis (bTB) susceptibility 31) . The association studies of BoLA-DRB3 and economic traits and disease are summarized in Table 2.…”
Section: Association Of With Cattle Economic Traits and Diseasesmentioning
confidence: 99%